The Use of Bone Graft Substitute in Hand Surgery: A Prospective Observational Study. Issue 24 (June 2016) - Liodaki, Eirini; Kraemer, Robert; Mailaender, Peter; Stang, Felix
Abstract : Abstract: Bone defects are a very common problem in hand surgery, occurring in bone tumor surgery, in complicated fractures, and in wrist surgery. Bone substitutes may be used instead of autologous bone graft to avoid donor site morbidity. In this article, we will review our experience with the use of Cerament bone void filler (Bonesupport, Lund, Sweden) in elective and trauma hand surgery. A prospective clinical study was conducted with 16 patients treated with this bone graft substitute in our department over a period of 3.5 years. Twelve patients (2 female, 10 male; with an average age of 42.42 years) with monostoic enchondroma of the phalanges were treated and 4 patients (1 female, 3 male; with an average age of 55.25 years) with complicated metacarpal fractures with bone defect. Data such as postoperative course with rating of pain, postoperative complications, functional outcome assessment at 1, 2, 3, 6 months, time to complete remodeling were registered. Postoperative redness and swelling after bone graft substitute use was noticed in 7 patients with enchondroma surgery due to the thin soft-tissue envelope of the fingers. Excellent total active motion of the involved digit was noticed in 10 of 12 enchondroma patients and in all 4 fracture patients at 2-month follow-up. In summary, satisfying results are described, making the use of injectable bone graft substitute in the surgical treatment of enchondromas, as well as in trauma hand surgery a good choice.